Marked and unmarked thematization patterns: A comparative analysis of persuasive texts written by American columnists and their Persian translations - Mardani, Tooba (Yayasan Mitra Persada Nusantara, 2024)
Thematization is the process of arranging theme, rheme patterns in a text. It is considered the mental act or process of selecting particular topics as themes in discourse or words as themes in sentences. This paper examines thematization strategies in English opinion articles and compares them with their Persian translations. To this end, one of the leading newspapers in the United States, The New York Times, was chosen. Based on the qualitative and quantitative analysis of textual features and marked and unmarked themes of 6 opinion articles and their Persian translations, this study aimed to find out how the translators organize their themes into marked and unmarked ones and how these organizations are related to the original texts. The findings revealed that thematization patterns can help the understanding of the texts. The results for the marked and unmarked thematization patterns were relatively the same in the original texts and their translations.